PENGEMBANGAN MEDIA BUKU SAKU LITERASI ANAK BERBASIS CERITA LOKAL UNTUK MENINGKATKAN PEMAHAMAN BACAAN PADA SISWA KELAS III DI SDN 06 KOTABARU - Kurniati, Agusta; Serani, Gabriel; Maulidiyanti, Ulfa (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2026)
This study aimed to develop a pocketbook learning medium for children’s literacy based on local stories to improve reading comprehension among third-grade students at SD Negeri 06 Kotabaru. The research employed the 4D development model, consisting of Define, Design, Develop, and Disseminate stages. The product developed was a 15×15 cm pocketbook containing five local stories from Kotabaru, complemented with engaging illustrations, moral values, and content adjusted to elementary students’ comprehension levels. Data were collected through observation, interviews, and tests (pretest and posttest). Validation by material and media experts indicated that the product met the criteria of content feasibility, presentation, language, and graphics. The results showed that the pocketbook was categorized as very feasible, with media expert validation at 93.75% and material expert validation at 95.83%. It was also considered very practical, with scores of 87.5% (limited scale) and 81.6% (wider scale). In terms of effectiveness, it showed a moderate improvement in students’ reading comprehension, with N-gain scores of 0.45 (limited scale) and 0.31 (wider scale). In conclusion, the local story-based literacy pocketbook is feasible, practical, and effective in improving students’ reading comprehension. This study contributes to the development of local wisdom-based learning media and serves as a reference for literacy learning innovation in elementary schools.